Self-sufficient nanoparticles with dual-enzyme activity trigger radical storms and activate cascade-amplified antitumor immunologic responses - Liping Bai; Jin Yang; Siting Yu; Zhongzheng Xiang; Yuanyuan Zeng; Meiling Shen; Xiaorong Kou; Qinjie Wu; Changyang Gong (Elsevier, 2024)
Radiotherapy (RT) can potentially induce systemic immune responses by initiating immunogenic cell death (ICD) of tumor cells. However, RT-induced antitumor immunologic responses are sporadic and insufficient against cancer metastases. Herein, we construct multifunctional self-sufficient nanoparticles (MARS) with dual-enzyme activity (GOx and peroxidase-like) to trigger radical storms and activate the cascade-amplified systemic immune responses to suppress both local tumors and metastatic relapse. In addition to limiting the Warburg effect to actualize starvation therapy, MARS catalyzes glucose to produce hydrogen peroxide (H2O2), which is then used in the Cu+-mediated Fenton-like reaction and RT sensitization. RT and chemodynamic therapy produce reactive oxygen species in the form of radical storms, which have a robust ICD impact on mobilizing the immune system. Thus, when MARS is combined with RT, potent systemic antitumor immunity can be generated by activating antigen-presenting cells, promoting dendritic cells maturation, increasing the infiltration of cytotoxic T lymphocytes, and reprogramming the immunosuppressive tumor microenvironment. Furthermore, the synergistic therapy of RT and MARS effectively suppresses local tumor growth, increases mouse longevity, and results in a 90% reduction in lung metastasis and postoperative recurrence. Overall, we provide a viable approach to treating cancer by inducing radical storms and activating cascade-amplified systemic immunity.